The Relationship between Forest and Land Rehabilitation with the Quality and Health of Watershed - wahyudi susanto (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2019)
This study estimates the relationship between Forest and Land Rehabilitation policies and the quality and health of watersheds measured by the Coefficient of Flow Regime. The method used is the estimation of the Granger causality relationship. The results of this study indicate that in the short term or less than three years of forest and land rehabilitation does not have a significant relationship with the good value of the coefficient of flow regime. It is hoped that with these findings, the government can review the methodology, institutional system, location, quality of materials and tools for forest and land rehabilitation by taking into account the natural and geographical conditions around the watershed. furthermore, the government can implement other measures to support forest and land rehabilitation in accordance with existing regulations.